2021
DOI: 10.32598/ijpcp.26.3.2325.2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Emotional Regulation in Males With Internet Addiction, Food Addiction, Opioid Dependence and Normal Peers

Abstract: Objectives: Difficulty in emotional regulation is an important component in the pathology of different types of addiction and its evaluation can be helpful in understanding and treating these difficulties. The purpose of this study is to evaluate emotional regulation in people with opioid dependence (heroin and opium), food addiction, and internet addiction compared to normal people. Methods: This is a causal- comparative study. Participants were 120 eligible male addicts selected using a purposive sampling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…The result about metacognition is in agreement with previous results (Castro Muñoz et al, 2021;Lenzo et al, 2020;Nameni et al, 2017;Palmieri et al, 2021;Cinar & Schou, 2014) and the result about emotion regulation training is in agreement with that of other studies (Miller et al, 2018;Morawetz et al, 2020;Pachón-Basallo et al, 2021;Steward et al, 2019;Gomez & Perez, 2020;Isasi et al, 2013;Ferrer & Mendez, 2018;Babaei et al, 2021). To explain the results obtained about metacognitive training, it can be said that according to the theory of self-regulation of executive function (S-REF), metacognitive training affects self-regulation through negative relationship with cognitive attention syndrome (CAS) and self-regulation has a positive relationship with selfefficacy (Kaplan, 2008;Salari Far & Mazaheri, 2010;Cera et al, 2013;Pour vakhshoori et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…The result about metacognition is in agreement with previous results (Castro Muñoz et al, 2021;Lenzo et al, 2020;Nameni et al, 2017;Palmieri et al, 2021;Cinar & Schou, 2014) and the result about emotion regulation training is in agreement with that of other studies (Miller et al, 2018;Morawetz et al, 2020;Pachón-Basallo et al, 2021;Steward et al, 2019;Gomez & Perez, 2020;Isasi et al, 2013;Ferrer & Mendez, 2018;Babaei et al, 2021). To explain the results obtained about metacognitive training, it can be said that according to the theory of self-regulation of executive function (S-REF), metacognitive training affects self-regulation through negative relationship with cognitive attention syndrome (CAS) and self-regulation has a positive relationship with selfefficacy (Kaplan, 2008;Salari Far & Mazaheri, 2010;Cera et al, 2013;Pour vakhshoori et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Babaei et al found that emotional regulation was related to different addictions, such as Internet addiction, food addiction and opioid addiction [22]. Similarly, Trumello et al argued that excessive Internet use may be an attempt by people to avoid dealing with negative emotions as it allows instant emotional avoidance, as well as distraction and disconnection [23].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also established a relationship between difficulties in emotional regulation, such as a poor ability to understand, control and manage negative emotions, and problematic Internet use in young students, specifically, a preference for online social interactions [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Así mismo también se ha demostrado que la adicción hacia el internet llega a provocar efectos negativos en las personas, es decir problemas de conducta y de los impulsos, conflictos y discusiones en las relaciones interpersonales (Mufasa y Aysan, 2017; Neverkovich et al, 2017). El problema es real, ya que según algunos estudios la adicción hacia el internet es similar a la adicción hacia los alimentos debido al abuso de sustancias, así como el abuso de su uso, por el cual llega a tener una conducta como la regulación emocional (Babaei et al, 2021;Romero Rodríguez et al, 2021).…”
Section: Introductionunclassified